Transformation of valuable orientations of students in a social crisis - V. Semychenko; A. Chumak (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article points out the tendencies of development of system of values of the students in the conditions of active socio-political changes. Students' attitudes to actual components of their life are revealed on the basis of incomplete sentences method, followed by content analysis. The answers given by students in the conditions of a peace condition of society (2012, 2013) and in the conditions of crisis (2014) are compared.
Keywords: student's youth; system of values; crisis state of society; youth's attitude to society; state; higher education; educational innovations; professions; availability of life ideals